Accounting Information System of Medicinal Supply in Pharmacy in Langkat District North Sumatra Indonesia - Lores, Linda (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The role of pharmacies is very important in developing human health and improving people’s quality of life. The purpose of this research is to determine the influence of accounting and inventory management information systems on the operational performance of private pharmacies in Deliserdang district, North Sumatra. As well as knowing the perceptions of private pharmacy owners and employees regarding the use of accounting information systems in managing drug supplies. Quantitative methods were used by distributing questionnaires and conducting interviews with several respondents. Using multiple linear regression and SPSS to process research data. The research results found that accounting information systems  had a positive and significant effect on operational performance, and operational management had an effect on operational performance. Another pharmacy finding states that the accounting information system is very helpful in determining drug inventory policies to avoid risks, facilitate drug inventory management, and improve the performance of manual pharmacies, because, regarding the risks that will be faced, inventory management errors will also have a negative impact on customer safety. Medicines that have an expiry date, customer service, medicine stock, employee competence in using technology, and knowledge about medicines are also very important.